Investigation of Predictors to Achieve Acceptable Lung Dose in T-Shaped Upper and Middle Esophageal Cancer With IMRT and VMAT - Shao, Yan; Chen, Hua; Wang, Hao; Duan, Yanhua; Feng, Aihui; Huang, Ying; Gu, Hengle; Kong, Qing; Xu, Zhiyong (Frontiers in Oncology, 2021)
Purpose: The purpose of this study is to investigate whether there were predictors and cut-off points can predict the acceptable lung dose using IMRT and VMAT in radiotherapy for upper ang middle esophageal cancer. Material and Methods: 82 patients with T-shaped upper-middle esophageal cancer (UMEC) were enrolled in this retrospective study. Jaw-tracking IMRT plan (JT-IMRT), Full-arc VMAT plan (F-VMAT), and Pactial-arc VMAT plan (P-VMAT) were generated for each patient. Dosimetric parameters such as MLD, V20 of total lung were compared among the three plannings. Ten factors such as PCTVinferior length and PCTVinferior length/total lung length were calculated to find the predictors and cut-off points of the predictors. All patients were divided into two groups according to the cut-off points, and the dosimetric differences between the two groups of the three plans were compared. ANOVA, Receiver operating characteristic (ROC) analysis, and Mann-Whitney U test were performed for comparisons between datasets. A P <0.05 was considered statistically significant. Result: The quality of the targets of the three plannings was comparable. The total lung dose in P-VMAT was significantly lower than that in JT IMRT and F-VMAT. MU of F-VMAT and P-VMAT was significantly lower than that of JT IMRT. ROC analysis showed that among JT IMRT, F-VMAT and P-VMAT, PCTVi-L and PCTVi-L/TLL had diagnostic power to predict the suitability of RT plans according to lung dose constraints of our department. For JT IMRT, the cut-off points of PCTVi-L and PCTVi-L/TLL were 16.6 and 0.59. For F-VMAT, the cut-off points of PCTVi-L and PCTVi-L/TLL were 16.75 and 0.62. For P-VMAT, the cut-off points of PCTVi-L and PCTVi-L/TLL were 15.15 and 0.59. After Mann-Whitney U test analysis, it was found that among the three plannings, the group with lower PCTVi-L and PCTVi-L/TLL could significantly reduce the dose of total lung and heart (p <0.05). Conclusion: PCTVi-L <16.6 and PCTVi-L/TLL < 0.59 for JT IMRT, PCTVi-L <16.75 and PCTVi-L/TLL < 0.62 for F-VMAT and PCTVi-L <15.15 and PCTVi-L/TLL < 0.59 for P-VMAT can predict whether patients with T-shaped UMEC can meet the lung dose limits of our department.